Screening and characterization of biocontrol bacteria isolated from Ageratum conyzoides against Collectotrichum fructicola causing Chinese plum (Prunus salicina Lindl.) anthracnose - Chen, Xiaolin; Zhang, Miaomiao; Tang, Lihua; Huang, Suiping; Guo, Tangxun; Li, Qili (Frontiers in Microbiology, 2023)
Chinese plum (Prunus salicina Lindl.) is a nutritionally and economically important stone fruit widely grown around the world. Anthracnose, caused by Collectotrichum spp., is one of the primary biotic stress factors limiting plum production. Medicinal plants may harbor rhizospheric or endophytic microorganisms that produce bioactive metabolites that can be used as anthracnose biocontrol agents. Here, 27 bacterial isolates from medicinal plant A. conyzoides with diverse antagonistic activities against C. fructicola were screened. Based on morphological, physiological, biochemical, and molecular characterization, twenty-five of these isolates belong to different species of genus Bacillus, one to Pseudomonas monsensis, and one more to Microbacterium phyllosphaerae. Eight representative strains showed high biocontrol efficacy against plum anthracnose in a pot experiment. In addition, several Bacillus isolates showed a broad spectrum of inhibitory activity against a variety of fungal phytopathogens. Analysis of the volatile organic compound profile of these eight representative strains revealed a total of 47 compounds, most of which were ketones, while the others included alkanes, alkenes, alcohols, pyrazines and phenols. Overall, this study confirmed the potential value of eight bacterial isolates for development as anthracnose biocontrol agents.